MODEL PENDIDIKAN KARAKTER RELIGIUS DALAM PERSPEKTIF SYAIH MUSTHOFA AL-GHALAYAINI - Muhammad Minan Nur Rohman; Ahmad Ma'ruf (Universitas Yudharta Pasuruan, 2020)
Religus character education as outlined in Syaih Musthofa Al-Ghlayini in the book Idhatun Nansyi'in is in accordance with what was written by Edy Suparjan, in his book entitled historical education to shape the nation's character, which is explained in the book there are educational character values which refers to the standard 100 famous figures of the world. The method of this research is library research, which means a study by studying books, manuscripts, or magazines that come from literature that is relevant to the issues raised in the study. The results of the character education model in the perspective of Syaih Musthofa Al-Ghalayaini are: First, children must have sincerity. Both students must have patience. The three students must care about each other. Fourth as students must be able to start themselves, especially others. The five students must practice their religion well. The six students as participants must keep their promises. Go as students to help one another. Eighth as students must be generous. The nine students must have a positive nature of thinking or always trying. The results of the character education model in the perspective of Syaih Musthofa Al-Ghalayaini are: First, children must have sincerity. Both students must have patience. The three students must care about each other. Fourth as students must be able to start themselves, especially others. The five students must practice their religion well. The six students as participants must keep their promises. Go as students to help one another. Eighth as students must be generous. The nine students must have a positive nature of thinking or always trying